Hydraulic characteristics of the wooden-paddle pump - Subin Pinkayan; Prof. M. R. Carstens; Prof. Franklin O. Rose; Prof. A. D. Benham; T. H. Evans, Dean (Bangkok : SEATO Graduate School of Engineering, 1961)
Wooden-paddle pumps are used extenstively throughout Thailand for supplying irrigation water to rice fields, Therse low-head pumps consist of an endless chain of wooden paddles which are oulled up a rectangular wooden trough. the lower end of the trough is submerged in the waer to be pumped. The Performance characteristics of this type of pump were experimentally determined in the Hydraulics Laboratory of the SEATO Graduate School of Engineering. The independent variables were intake submergence and angle of inclination. The tests were performed with a single pump operationg at a fixed value of paddle velocity. The test results showed that the pum is surprisingly efficient, about 40 percent, regardless of the angle of inclination. The pump discharge was found to depend primarily upon the submergence of the intake within the limits of the test program.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in the SEATO Graduate School of Engineering, Bangkok, Thailand.
Thesis (M.Eng.) - SEATO Graduate School of Engineering
Keywords: Pumping machinery